Marginal Keratitis with Secondary Diffuse Lamellar Keratitis After Small Incision Lenticule Extraction (SMILE) After Initiation of Continuous Positive Airway Pressure (CPAP) Therapy - Moshirfar, Majid (Int Med Case Rep J, 2020)
Marginal keratitis, also known as catarrhal infiltrates, is a common, self-limiting condition characterized by inflammation at the peripheral aspect of the cornea. This non-infectious process is most typically a reaction to bacteria such as Staphylococcus, and results from a cell-mediated immune response to the bacterial antigens. This hypersensitivity reaction leads to the formation of stromal infiltrates that run parallel to the limbus. These infiltrates may extend around the limbal edge and can lead to the formation of marginal ulcers. Often the patient will have associated blepharoconjunctivitis. Both marginal keratitis and blepharoconjunctivitis are treated with topical steroids, with or without antibiotics, and good lid hygiene. We report a case of a patient who previously underwent small incision lenticule extraction (SMILE) who presented with marginal keratitis and secondary diffuse lamellar keratitis (DLK) in the right eye following recent initiation of continuous positive airway pressure (CPAP) therapy. There was no antecedent ocular trauma. With the initiation of steroid therapy, the patient returned to baseline visual acuity within one week. Though recurrence may be common in cases of marginal keratitis, our patient has not had any recurrence of symptoms or disease. DLK has previously been reported in the literature; however, there has been no reported case of marginal keratitis with secondary DLK after initiation of CPAP therapy to date.